2001
DOI: 10.1097/00003246-200108000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma clearance of iodine contrast media as a measure of glomerular filtration rate in critically ill patients

Abstract: These findings indicate that the determination of plasma clearance of iohexol/iopromide is a simple, rapid, and accurate method that can indeed be used for estimating GFR in ICU patients with normal renal function or even different degrees of renal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 23 publications
4
68
0
Order By: Relevance
“…Erley et al (10) have measured GFR by nonradioactive radiocontrast in critically ill patients using a single injection technique and found good correlation between inulin clearance and limited sampling single shot plasma clearance technique. These authors used radiographic fluorescence, which is less sensitive than the HPLC technique and requires administration of large volume of radiocontrast (11).…”
Section: Plasma Clearance Methodsmentioning
confidence: 99%
“…Erley et al (10) have measured GFR by nonradioactive radiocontrast in critically ill patients using a single injection technique and found good correlation between inulin clearance and limited sampling single shot plasma clearance technique. These authors used radiographic fluorescence, which is less sensitive than the HPLC technique and requires administration of large volume of radiocontrast (11).…”
Section: Plasma Clearance Methodsmentioning
confidence: 99%
“…In practice, the major peak, eluting at about 5 min, is used for determining serum/plasma concentrations [69]. Most studies indicate close agreement between GFR (measured by inulin clearance) and clearance of iohexol, measured as standard renal clearance or plasma disappearance [65,[69][70][71][72]. There is not only a very good correlation between plasma iohexol clearance and that of 51 Cr-EDTA, but also no difference between the methods by Bland-Altman analysis [73].…”
Section: Iohexolmentioning
confidence: 99%
“…Several investigators have demonstrated real-time changes in renal function using thermodilution techniques, although this is an invasive procedure, requiring placement of a catheter in the renal vein (62). Others have shown a strong correlation between sparse blood sampling after administration of iodinated contrast compared with the gold standard of inulin clearance (63), although concerns about the use of contrast in the context of patients who are at risk for AKI suggest a limited role for this approach. Others have looked at radioactive and nonradioactive means of continuously monitoring renal function in the ICU (15), including a noninvasive bedside radiation detector the size of an automated BP cuff (64).…”
Section: Early Recognition Of Renal Damage and New Biomarkersmentioning
confidence: 99%